The tiger rising - DiCamillo, Kate. (Sommerville, Mass. Candlewick press, 2001)
Rob, who passes the time in his rural Florida community by wood carving, is drawn by his spunky but angry friend Sistine into a plan to free a caged tiger.
Keywords: Tiger -- Fiction; Animals -- Treatment -- Fiction; Wood carving -- Fiction; Friendship -- Fiction; Florida -- Fiction